Penyuluhan Fiqh Ibadah tentang Syarat-Syarat Sah Sholat untuk Meningkatkan Pengetahuan Jama’ah Masjid Al-Hikmah Desa Sekuning Besowo Kediri - Fatikahatun Nikmah; Reni Imawan (LP3M IAIFA Kediri, 2023)
The material of fiqh is basically related to sharia in Islam both related to worship and muamalah. Fiqh material related to shari'ah and practice automatically indicates the existence of material related to humans. Therefore, in the delivery does not rely on classical methods such as lectures, but there must be an active role of mosque congregation themselves. In the study itself the author chose to use the PAR (Participatory Action Research) method. The results of this study, do some of the following steps; The first step we do is to prepare the material that we will deliver. The second step is to need methods and approaches that are flexible according to the circumstances. Because, there is often a gap between plans and practices on the ground. The third step is to evaluate the counseling that has been carried out from start to finish to mosque congregation. This is in an attempt to find out the extent of the material that has been captured by mosque congregation while during counseling.